2014
DOI: 10.1021/jm5006918
|View full text |Cite
|
Sign up to set email alerts
|

Promiscuity and Selectivity in Covalent Enzyme Inhibition: A Systematic Study of Electrophilic Fragments

Abstract: Covalent ligand-target interactions offer significant pharmacological advantages. However, off-target reactivity of the reactive groups, which usually have electrophilic properties, must be minimized, and the selectivity of irreversible inhibitors is a crucial requirement. We therefore performed a systematic study to determine the selectivity of several electrophilic groups that can be used as building blocks for covalently binding ligands. Six reactive groups with modulated electrophilicity were combined with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(107 citation statements)
references
References 54 publications
(76 reference statements)
4
101
0
2
Order By: Relevance
“…The dependency of the observed reactivity of individual fragments on the structure of the reacting protein is also underlined by the observation that the determined proteomic reactivity is not at all related to binding to glutathione, a result that is well in line with the previous report by Jçst et al [8] Glutathione is the ubiquitous tripeptide Glu-Cys-Gly, which is present in cells in millimolar concentrations. Assays to check the reactivity of potentially reactive compounds are a standard method in the pharmaceutical industry to evaluate the degree of promiscuity of a potentially thiol-reactive molecule and to estimate the risk for induction of liver toxicity.…”
supporting
confidence: 87%
“…The dependency of the observed reactivity of individual fragments on the structure of the reacting protein is also underlined by the observation that the determined proteomic reactivity is not at all related to binding to glutathione, a result that is well in line with the previous report by Jçst et al [8] Glutathione is the ubiquitous tripeptide Glu-Cys-Gly, which is present in cells in millimolar concentrations. Assays to check the reactivity of potentially reactive compounds are a standard method in the pharmaceutical industry to evaluate the degree of promiscuity of a potentially thiol-reactive molecule and to estimate the risk for induction of liver toxicity.…”
supporting
confidence: 87%
“…Recent studies are consistent with this notion, demonstrating the value of incorporating electrophilic reactivity into reversible and irreversible inhibitor design. 9,10 A previous study from our group showed that a high rate of compound reactivity with GSH has correlated with high covalent binding burdens in hepatocytes. 11 In addition, the extent of covalent binding burden observed in hepatocytes combined with the daily dose of drug are predictive of human hepatotoxicity.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Covalent inhibitors generally display a range of attractive features, including high potency, prolonged duration of action, and amenability to rational design. A systematic study has recently shown that even reactive electrophiles, such as the Michael acceptor acrylamide, do not react indiscriminately with any biological nucleophile [14]. This differential reactivity can be harnessed for the development of covalent inhibitors, especially those that target non-catalytic residues [15].…”
Section: Introductionmentioning
confidence: 99%